Synthesis of Diisocyanate‐Containing Thiophenes and Their Use in PDMS‐Based Segmented Polymers. Issue 1 (4th December 2015) - Grübel, Matthias; Meister, Simon; Schulze, Ulrich; Raftopoulos, Konstantinos N.; Baumer, Franziska; Papadakis, Christine M.; Nilges, Tom; Rieger, Bernhard
Abstract : A synthesis route to siloxane‐based thermoplastic elastomers (TPE) with functional hard blocks is described. The photophysical functionality is provided by oligothiophenes, namely terthiophene and bithiophene. Polyaddition of isocyanate‐bearing thiophenes and amine‐terminated siloxanes yields polymers incorporating a bisurea structure motive. Phase separation and strong hydrogen bonds provide ordering of the thiophenes, which is shown by wide‐angle X‐ray scattering (WAXS) and X‐ray powder diffraction (XRD). Fluorescence measurements reveal a strong red shift of emission of polymer films compared with polymer solutions, thus confirming the existence of hard block segments with an enhanced π system and higher charge–carrier mobility. Tuning of the optical band gap by different polymer compositions and various post polymerization treatments is demonstrated. Abstract : Stacking of thiophene units within siloxane‐based polymers is supported by hydrogen bonds of urea groups. A phase separation is presented. Because of the stacking the fluorescence of the polymer materials is shifted to higher wavelengths. This effect can be used to analyze microcrystals in polymers.